2016
DOI: 10.1016/j.prevetmed.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A register-based study of the antimicrobial usage in Danish veal calves and young bulls

Abstract: High antimicrobial usage and multidrug resistance have been reported in veal calves in Europe. This may be attributed to a high risk of disease as veal calves are often purchased from numerous dairy herds, exposed to stress related to the transport and commingling of new animals, and fed a new ration. In this study, we used national register data to characterize the use of antimicrobials registered for large Danish veal calf and young bull producing herds in 2014. A total of 325 herds with veal calf and potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
(51 reference statements)
0
26
0
Order By: Relevance
“…As previously observed, respiratory diseases are the main indication for AMU (Pardon et al, 2012a;Fertner et al, 2016;Lava et al, 2016b). Logically, initial empirical treatment was directed toward Mycoplasma bovis, the dominant respiratory pathogen in veal systems (Pardon et al, 2011), which may have reduced the need for retreatment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As previously observed, respiratory diseases are the main indication for AMU (Pardon et al, 2012a;Fertner et al, 2016;Lava et al, 2016b). Logically, initial empirical treatment was directed toward Mycoplasma bovis, the dominant respiratory pathogen in veal systems (Pardon et al, 2011), which may have reduced the need for retreatment.…”
Section: Discussionmentioning
confidence: 94%
“…Available studies on AMU in different species all demonstrate the large variation in usage, with farms hardly using any antimicrobials and others very intensively (Timmerman et al, 2006;Pardon et al, 2012a;Agunos et al, 2017). In other words, there appears to be a major window of opportunity to reduce usage, but the factors driving AMU in the veal industry are poorly understood (Fertner et al, 2016;Lava et al, 2016b;Jarrige et al, 2017). Knowledge on these drivers is essential to design effective campaigns and intervention measures to rationalize AMU in the short term and for the development of sustainable veal production systems in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, vaccines are routinely recommended and applied in livestock production systems (Codes of Practice for the care and handling of farm animals [n.d.]; https://www.nfacc.ca/codes-of-practice). Studies have reported the relationship between vaccination and antimicrobial use (Del Pozo Sacristán, Michiels, Martens, Haesebrouck, & Maes, ; Fertner, Toft, Martin, & Boklund, ; Lava, Schüpbach‐Regula, Steiner, & Meylan, ); however, an assessment of these combined actions on the occurrence of resistance has not been published to our knowledge. The absence of vaccination and other nonantimicrobial use factors at the farm level of the agri‐food chain in this review represents an important data gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Very precise follow-up and 292 measurement of the temperature of every calf, when even only slightly suspected, could have contributed to 293 the extensive antimicrobial usage, although NSAIDs alone were used for mildly sick calves with elevated 294 temperature. Antimicrobials were used in our study mostly to treat respiratory disease, similarly as for calves 295 in Denmark (Fertner et al, 2016), other indications being recorded only occasionally. were male, for which the care on source farms is sometimes questioned.…”
Section: Use Of Antimicrobials 290mentioning
confidence: 99%